Development of α-Tocopherol Succinate-Based Nanostructured Lipid Carriers for Delivery of Paclitaxel - Sushrut Marathe; Gauri Shadambikar; Tabish Mehraj; Suresh P. Sulochana; Narendar Dudhipala; Soumyajit Majumdar (MDPI AG, 2022)
The management of retinoblastoma (RB) involves the use of invasive treatment regimens. Paclitaxel (PTX), an effective antineoplastic compound used in the treatment of a wide range of malignant tumors, poses treatment challenges due to systemic toxicity, rapid elimination, and development of resistance. The goal of this work was to develop PTX-loaded, α-tocopherol succinate (αTS)-based, nanostructured lipid carrier (NLCs; αTS-PTX-NLC) and PEGylated αTS-PTX-NLC (αTS-PTX-PEG-NLC) to improve ocular bioavailability. The hot homogenization method was used to prepare the NLCs, and repeated measures ANOVA analysis was used for formulation optimization. αTS-PTX-NLC and αTS-PTX-PEG-NLC had a mean particle size, polydispersity index and zeta potential of 186.2 ± 3.9 nm, 0.17 ± 0.03, −33.2 ± 1.3 mV and 96.2 ± 3.9 nm, 0.27 ± 0.03, −39.15 ± 3.2 mV, respectively. The assay and entrapment efficiency of both formulations was >95.0%. The NLC exhibited a spherical shape, as seen from TEM images. Sterilized (autoclaved) formulations were stable for up to 60 days (last time point checked) under refrigerated conditions. PTX-NLC formulations exhibited an initial burst release and 40% drug release, overall, in 48 h. The formulations exhibited desirable physicochemical properties and could lead to an effective therapeutic option in the management of RB.